Experience of endomyocardial biopsy from a tertiary care center in India. (July 2021) - Nakra, Tripti; Arava, Sudheer; Seth, Sandeep; Ojha, Vineeta; Jagia, Priya; Ray, Ruma
Background: Endomyocardial biopsy is the gold standard and has a definite role in the surveillance of cardiac allograft rejection. Its role in other cardiac diseases is limited. However, it is required for conclusive diagnosis of a few entities in which it can influence patient management. There is no reported data regarding the utility of endomyocardial biopsy in the Indian population. Thus, this study was undertaken in a tertiary care center in India to assess the utility of endomyocardial biopsy in various cardiac diseases in the context of clinical diagnoses. Methods: All endomyocardial biopsies conducted over a 27-year period were evaluated. Clinical details including indication for biopsy were collected. Histopathological findings were recorded and classified as definitive diagnosis, probable diagnosis with features consistent with the clinical diagnosis, and nonspecific morphological findings. Results: A total of 927 endomyocardial biopsies from 719 patients were reviewed. Endomyocardial biopsy was diagnostic in 12.5% of native cardiac biopsies and 52.1% showed nondiagnostic findings. The most frequent diagnoses were amyloidosis (58.7%) and myocarditis (8.6%). Endomyocardial biopsy had a diagnostic role in evaluation of restrictive cardiac diseases. Endomyocardial fibrosis and tubercular myocarditis, relatively more prevalent in the Indian population, were also identified. Cases of rheumatic heart disease, desmin cardiomyopathy, and microfibrillar cardiomyopathy were surprise findings, proving the usefulness of endomyocardial biopsy in detecting some rare cardiac conditions. Conclusion: Endomyocardial biopsy is an important tool for the diagnosis of specific cardiac diseases including some rare entities, and for conditions which are more prevalent in our country, requiring biopsy confirmation.